Alternative splicing of tumour-related Rac1b in colorectal cells is regulated by protein phosphorylation of splicing factor SRSF1 - Gonçalves, Vânia (2014)
Abstract publicado em: 1st ASPIC International congress: proceedings book, p. 56. Disponível em: http://1stcongress.aspic.pt/sites/default/files/proceedins_book_web.2.pdf